2007
DOI: 10.1088/1751-8113/40/43/008
|View full text |Cite
|
Sign up to set email alerts
|

Nodal points and the transition from ordered to chaotic Bohmian trajectories

Abstract: We explore the transition from order to chaos for the Bohmian trajectories of a simple quantum system corresponding to the superposition of three stationary states in a 2D harmonic well with incommensurable frequencies. We study in particular the role of nodal points in the transition to chaos. Our main findings are (a) a proof of the existence of bounded domains in configuration space which are devoid of nodal points, (b) an analytical construction of formal series representing regular orbits in the central d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(107 citation statements)
references
References 38 publications
4
93
0
10
Order By: Relevance
“…In a series of works published later on by Wisniacki and coworkers [282,283] it was shown that the origin of Bohmian chaos is in the evolution in time of those vortices. An analogous conclusion was also found by Efthymiopoulos and coworkers [197,[284][285][286][287], who showed that chaos is due to the presence of moving quantum vortices forming nodal point-X-point complexes. In particular, in reference [197] a theoretical analysis of the dependence of Lyapunov exponents of Bohmian trajectories on the size and speed of the quantum vortices is presented, which explains their earlier numerical findings [284,285].…”
Section: Role Of Vortical Dynamicssupporting
confidence: 81%
“…In a series of works published later on by Wisniacki and coworkers [282,283] it was shown that the origin of Bohmian chaos is in the evolution in time of those vortices. An analogous conclusion was also found by Efthymiopoulos and coworkers [197,[284][285][286][287], who showed that chaos is due to the presence of moving quantum vortices forming nodal point-X-point complexes. In particular, in reference [197] a theoretical analysis of the dependence of Lyapunov exponents of Bohmian trajectories on the size and speed of the quantum vortices is presented, which explains their earlier numerical findings [284,285].…”
Section: Role Of Vortical Dynamicssupporting
confidence: 81%
“…These series are similar to Lindstedt series with fixed frequencies, or to the 'third integral' series of galactic dynamics (Contopoulos 1960). In Efthymiopoulos et al (2007) we demonstrated the consistency of the construction. Namely, contrary to the case of classical Lindstedt series, no secular terms appear in the quantum-mechanical series as a result of keeping the frequencies constant.…”
Section: Ordered Orbits and Their Formal Seriesmentioning
confidence: 66%
“…In the model (12) (Efthymiopoulos et al 2007), we find that the flow lines in the moving frame of reference (u, v) are spirals terminating at the nodal point. Furthermore, one spiral is always connected to one of the invariant manifolds of a simply hyperbolic point (called 'X-point') that exists in the vicinity of the nodal point.…”
Section: Nodal Point-x-point Complex and The Generation Of Chaosmentioning
confidence: 95%
See 2 more Smart Citations